Comparison of grain yield and quality of different types of japonica rice cultivars in the northern Jiangsu plain, China - Jin-long BIAN; Gao-lei REN; Fang-fu XU; Hong-cheng ZHANG; Hai-yan WEI (Journal of Integrative Agriculture)
In recent years, an increasing number of different types of japonica rice cultivars have been released in the southern rice region of China. The grain yield and quality of these new cultivars showed significant differences in large scale planting. However, the causes of the differences remain little known. Therefore, three typical types of japonica rice cultivars were used in this study to investigate their grain yield and quality. A scanning calorimeter (DSC), X-ray powder diffractometer (XRD), rapid viscosity analyzer (RVA) and taste analyzer were used to evaluate the cooking and eating properties. The results showed that the yield of non-soft hybrid japonica rice cultivars was significantly higher than that of non-soft inbred japonica rice cultivars and soft inbred japonica rice cultivars. Soft inbred japonica rice cultivars had a low amylose content and moderate protein content, which are the main reasons for the superior cooking and eating quality. In addition, the relative crystallinity of soft inbred japonica rice cultivars was significantly higher than that of non-soft inbred and non-soft hybrid japonica rice cultivars, which is considered the major factor resulting in higher transition temperature and gelatinization enthalpy (ΔHgel). Non-soft hybrid japonica rice cultivars had a higher number of large starch granules than soft inbred and non-soft inbred japonica rice cultivars. The setback value (SB) and breakdown value (BD), indirectly reflecting the cooking and eating quality of the three types of japonica rice cultivars, also confirmed that soft inbred japonica rice cultivars with a low SB value and a high BD value had better palatability than the other two types. This study provides guidance for future plantation of different types of japonica rice cultivars in large rice-producing areas.